The Role of Sustainability Perception in Consumer Behavior: A Study of Packaging, Ingredients, and Brand Awareness in the Soft Drinks Industry - Oh Zi Jian; Meenu Baliyan; Paul Dung Gadi; Serena Taherin A/P Siva-Muniandy; Salma Binti Azman; Salsabila Binti Mohamad Yusoff; Siti Nurhafiza Binti Mohamad Nadzri; Mani Bansal; Kuldeep Kumar; Kundan Pratap Srivastav; Daisy Mui Hung Kee (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2024)
This research seeks to understand how ingredients, packaging, brand awareness, and sustainability perception interact and influence consumer behavior in the soft drinks industry, specifically Coca-Cola. The online survey to 100 respondents was conducted via Google Form and the collective data was analyzed by the SPSS software. While the research examined the impact of ingredients and packaging on consumer decisions (H1 and H2), no direct effect was found. However, the research revealed a strong positive correlation between sustainability perception and consumer behavior (H3, R² = 0.391, beta = 0.423). Interestingly, a positive relationship emerged between packaging and ingredient impact on one hand, and sustainability perception on the other (H4, beta = 0.778). Additionally, sustainability perception was found to positively influence brand awareness (H5, beta = 0.548). These findings suggest that consumers prioritize sustainability when making purchasing decisions in the soft drinks industry, and that a brand's commitment to sustainable practices can indirectly influence consumer behavior through positive sustainability perception.